Osteocondrose em bovinos confinados - Marques, L. C. [UNESP]; Alessi, A. C.; Canola, J. C. [UNESP] (My University, 1998)
This paper reports the occurrence of osteochondrosis in feedlot cattle submitted to a high-caloric diet. About 11.6% of the animals showed symptoms that included lameness, tarsal hyperflexion, muscle fasciculations, reluctance to move and delayed recumbency. Necropsy and radiologic examination showed typical lesion of osteochondrosis, including cartilage discontinuity and osseous injury. The diet, age and high grow rate of the animals were considered to be factors in the development of osteochondrosis.
Osleochondrosis in feedlot cattle
Keywords: Cattle; Osteochondrosis